The Form, Meaning, and Function of Sasak Curing Mantras in Traditional Medicine in Benteng Selatan, Lendang Nangka Utara Village: Semantic Theoretical Approach - Minahasa, Windi Dani; Mahyuni; Lestari, Yuni Budi; Nuriadi (Journal of Authentic Research, 2026)
Traditional healing practices using mantras are still preserved by the Sasak people in Benteng Selatan Village, North Lendang Nangka, East Lombok. This study aims to describe the form, meaning, and function of Sasak healing mantras in traditional healing practices using a semantic theory approach. The method used is descriptive qualitative. Data collection techniques include in-depth interviews with three female traditional healers (belian), audio recordings of mantra chanting, field notes, and transcription. Data analysis techniques are carried out through four stages: identification of linguistic units in mantras, classification based on form, meaning, and function, description of semantic and stylistic features, and explanation using Émile Durkheim's functionalism theory. The results show that there are eight healing mantras that are still used to treat various diseases such as melihatk (disturbed spirits), kotong (burns/inflammation), stomach aches, broken bones, wounds, scorpion stings, crying babies, and childbirth. Structurally, these mantras are in the form of short lines (3–5 lines), have rhythmic patterns, repetition, and metaphors, and generally begin with Bismillahirrahmanirrahim. In terms of meaning, these mantras contain lexical and contextual meanings that symbolize purification, protection, exorcism of evil spirits, and restoration of physical and spiritual balance. Functionally, these mantras play a role in three aspects: spiritual (communication with divine powers), social (strengthening relationships between community members), and psychological (providing positive suggestions, calmness, and hope for healing). The implications of this research indicate that Sasak healing mantras are not merely traditional therapeutic tools, but also function as a medium for preserving local language, culture, and identity. This research contributes to the academic documentation of local knowledge and enriches linguistic studies, particularly in the fields of semantics and ethnolinguistics in the context of Indonesian culture.